Feed-in tariff policy in Hong Kong: Is it efficient? - Dato, Prudence; Durmaz, Tunc; Pommeret, Aude (ELSEVIER, 2021)
In this paper, we investigate whether the current feed-in tariff (FIT) policy in Hong Kong SAR can ensure the development of solar photovoltaic (PV) systems. To do so, we rely on the calibration of a dynamic model of household optimization. We account for the optimal residential consumer behavior under stochastic solar radiation to derive a break-even FIT, which we compare to the one in Hong Kong. Results show that the current FIT policy does not provide sufficient incentives to guarantee the development of solar PV installations. We calculate the break-even FIT for various solar PV and battery installation costs, payback periods, equipment lifetime, as well as the discount rate. We conclude by making recommendations for an efficient FIT policy in Hong Kong.
Keywords: Energy policy; Solar PV; Intermittency; Prosumers; Optimization; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences